The use of floating charge as an Islamic collateral instrument: a shariah compatibility analysis - Engku Ali, Engku Rabiah Adawiah; Mohd. Sulaiman, Aiman @ Nariman; Haron, Muhamad Nasir (International Islamic University Malaysia (IIUM), 2018)
The provision of collateral or security is imperative in modern banking as it serves as a significant form of risk mitigation against customer’s default in financing activities. One of the most common security instruments utilized by financial institutions is a charge. In the context of a client which is a body corporate, it may create either a fixed or a floating charge. A floating charge has some unique features whereby it constitutes a charge on a class of a company’s present and future assets. From the Shari’ah perspective, an Islamic financial institution’s collateral arrangements must primarily comply with the Shari’ah. The unique feature of a floating charge where the charged assets may constantly change from time to time may require thorough Shari’ah deliberation to determine its Shari’ah status. This paper specifically analyses floating charge from the Shari’ah perspective juxtaposing the discussion with the known legal characteristics of a floating charge under the law. The paper evaluates the compatibility of floating charge with the Shari’ah, using rahn contract and requirements as the benchmark framework. From the assessment, it is observed that a floating charge does not fulfil the rahn requirements as stipulated by the majority of jurists (Hanafi, Shafi’i and Hanbali). Nonetheless, the Maliki opinion tolerates the features of floating charge involving uncertain or unknown assets. In this regard, Maliki jurists are generally of the view that rahn is a secondary contract, hence, it remains valid even when there are gharar elements in the rahn asset. Another issue in a floating charge is the possibility of the charged assets becoming Shari’ah non-compliant or mixed with Shari’ah non-compliant assets in the future. The Malikis along with the majority of classical jurists do not allow rahn on impermissible assets. However, the paper finds some contemporary Shari’ah opinions arguing that they can still be used as marhun, provided that the prohibited elements are external and can be eliminated/excluded.